Temperature-programmed gas chromatography - Blumberg, Leonid M. (John Wiley, 2010)
This book introduces the reader to the basics concepts of temperature-programmed gas chromatography (GC), as well as the key properties of GC columns. It also discusses the mathematical and physical background of GC as well as the different aspects in the formation of a chromatogram, including retention times, peak spacing and peak widths